Meta-analysis of primary open versus closed cannulation strategy for totally implantable venous access port implantation - Klaiber, Ulla; Probst, Pascal; Hackbusch, Matthes; Jensen, Katrin; Dörr-Harim, Colette; Hüttner, Felix; Hackert, Thilo; Diener, Markus K.; Büchler, Markus W.; Knebel, Phillip (Langenbeck's archives of surgery, 2021)
There is still no reference standard for the implantation of totally implantable venous access ports (TIVAPs). A recently published multicentre randomised controlled trial (RCT) revealed a significantly greater risk of pneumothorax after closed cannulation than after an open strategy. The aim of this meta-analysis was to provide an update of the available evidence for the safety and effectiveness of primary open versus closed cannulation strategy.
Gesehen am 14.10.2021